RFID Technology Applications and Supply Chain Management: A Study on Manufacturing Sector in Malaysia - Thillai Raja Pertheban; Anbalagan Marimuthu; Kumara Rajah Venkatachalam (ExcelingTech, 2022)
Radio frequency identification (RFID) is an emerging commercial tool for many different elements of company, including supply chain management (SCM). RFID is a wireless non-contact system that uses radio-frequency electromagnetic fields to send data from a tag attached to an object for automatic identification and tracking. This technique is ideal for product distribution and tracking. RFID technology can be utilized in a variety of supply chain applications, including warehouse management, inventory management, freight transportation, manufacturing, and retailing. The supply chain can achieve excellent performance and tracking with RFID technology. This study investigated how RFID technology applications can help to improve supply chain management process in Malaysia's manufacturing sector. The research findings suggested that there is a beneficial relationship between RFID technology applications and supply chain management. The study's practical contributions include increasing SMEs' knowledge of RFID technology applications and performance of supply chain systems in the Klang Valley manufacturing industry, as well as increasing their competitiveness in domestic and international markets.